The Representation of Making in Urban Form - Murali Ramaswami; Llewellyn Seibold (Oz, 1989)
A concern for the order of urban form persists and is growing. In some cases this awareness has created new opportunities to establish or re-establish urban forms that have a great deal of value. In other instances a new formalism has come about which is as self-referential and abstract as the modernism it seeks to replace...